Analisis Citraan Pada Terjemahan Novel Al-Fatá al-ladhi Absara Lawnu al-Hawa: Tinjauan Stilistika - Ismail, Asnia Rahmawati; Wahyudi, Arif; Asnania, Aisya Putri; Satori, Achmad; Nurhuda, Zamzam; Suparno, Darsita (Kitabina: Jurnal Bahasa dan Sastra, 2023)
The research examines the issue of imagery in the translation of the novel "Al-Fatá al-ladhi Absara Lawnu al-Hawa." The objective of this study is to describe the various forms of imagery employed in the translation of the novel. The data collection methods utilized are literature review and note-taking. The data analysis method employed is descriptive analytics. The results of the data analysis are presented in an informal manner. The findings of the study indicate the presence of seven types of imagery in the translation of "Al-Fatá al-ladhi Absara Lawnu al-Hawa," namely visual imagery, auditory imagery, motion imagery, gustatory imagery, intellectual imagery, emotional imagery, and tactile imagery. Based on the data analysis, it was discovered that there are a total of seven types of imagery, with the following breakdown: 88 instances of visual imagery, 78 instances of auditory imagery, 97 instances of motion imagery, 23 instances of intellectual imagery, 3 instances of gustatory imagery, 102 instances of emotional imagery, 43 instances of tactile imagery, and 1 instance of olfactory imagery. These various forms of imagery add a distinct richness to the novel.